"A Place Belongs Forever": Telling Stories for the Personal Place Project. Issue 1 (2nd January 2020) - Zonn, Leo
Abstract : Stories people tell about places reflect identities of both, and it is suggested here that any understanding of their constitutive links should begin with personal accounts. The purpose of this article is to describe a format (the Personal Place Project) within which personal place-based stories are formulated and told, to provide illustrative vignettes that address these engagements, to direct attention to themes that arise in these descriptions, and to suggest paths to larger and more complex stories. Vignettes from 10 representative stories drawn from 152 undergraduate essays are presented. It is suggested that the deeply embedded and synergistic themes of Others, power, and identity may help illuminate the nature of these paths. I conclude that my future efforts should focus on the nature of my own positionalities which would allow me new insights into reading these stories within the chosen direction of social justice.